Plug in battery electric vehicle: design and integration of the braking system and drive train assembly - Ng, Wei Xuan (2016)
Global warming has always been a pressing problem. Furthermore with increasing amount of greenhouse gases in the atmosphere, it has caused drastic climate changes around the world. One of the biggest contributors of these pollutants being automobiles on the road. This is mainly due to internal combustion engine which uses fossil fuels as a source of energy. Therefore, various car manufactures have started build hybrid and full electric vehicles like BMW i8 and the revolutionary Tesla Model S.